Factors associated with students' assessment of teaching quality in a module in the MBCHB 1 program| - De Klerk, Brenda (University of the Free State, 2004)
In the light of a changed student body due to transformation principles coming into place and a new curriculum for undergraduate medical education introduced in 2000 in the Medical School of the University of the Free State, the obvious thing to do, was to take steps to ensure that the quality of the education and training students receive, was maintained at a high level. One way of ensuring quality was by having the modules in the program evaluated by students. However, the evaluations of modules in the M.B.,Ch.B. program that are in place (cf' Bezuidenhout 2000-2002), show big discrepancies between different classes, different language groups, different ages, etc. in their assessment of teaching and the curriculum in general. The problem addressed in this study dealt with factors coming into play when students in the M.B.,Ch.B. program evaluated a module. The following research questions were addressed: • How did the changes in the student body and the new curriculum affect the evaluation of modules? • Were there any student-related factors that might have influenced the students' way of evaluating the MED113 module's quality of instruction? • Were there specific people groups in the undergraduate medical education classes that needed special attention regarding certain aspects of teaching and training? • Were there any aspects regarding teaching or the lecturers in the MED113 module that drastically needed to be changed? The purpose of this study was to contribute to the quality of education in the M.B.,Ch.B. program of the School of Medicine, University of the Free State, and it aimed at gaining a better understanding of the results of the evaluation by students of the MED 113 module and to identify factors that might be associated with their evaluations. From students' evaluations, the weaknesses and strengths in the MED 113 module could also be established and corrected where necessary. The method of investigation entailed: • A literature study of quality assurance and the factors that could possibly play a role in students' assessments of lecture quality. • The development of a research instrument (questionnaire) for gathering data on students' perceptions of teaching quality in the MED113 (Concepts of Health and Disease) module for 2002, based on the information gathered from the literature review. These instruments were completed by each student after each session of the MED 113 module. • Factors influencing students' evaluation of teaching were identified, using the questionnaires (empirical study). • Recommendations regarding possible ways of addressing these factors that influence a student's perceptions were made. • The weaknesses and strengths, according to students' perception, in the MED 113 module, were identified by means of the questionnaire. • Recommendations to improve the teaching in the module were made, based on the findings. Information gained through this study will be used in the planning process for the MED113 module for 2004 and in future quality control strategies, with a view to improve the quality of teaching and learning in the School of Medicine at the University of the Free State.

In die lig van die veranderende studentesamestelling as gevolg van die transformasiebeginsels wat in werking gestel is en 'n nuwe kurrikulum vir voorgraadse studente wat sedert 2000 in werking is in die Skool vir Geneeskunde van die Fakulteit Gesondheidswetenskappe van die Universiteit van die Vrystaat, is die voorhandliggende ding om te doen, die daarstel van 'n behoorlike kwaliteitsversekeringsprogram om sodoende die kwaliteit van opleiding wat studente ontvang op 'n hoë vlak te verseker. Die logiese manier om kwaliteit te verseker was die daarstel van 'n evalueringsprogram waarin studente die modules evalueer. Dog die resultate van die evaluering van die M.B.,Ch.B.-program wat daargestel is (cf Bezuidenhout 2000-2002), het merkbare verskille getoon tussen verskillende klasse, verskillende taalgroepe, verskillende ouderdomme, ens. van studente in hulle evaluering van onderrig en die kurrikulum in die algemeen. Die probleem wat aangespreek word in hierdie studie handeloor die studentverwante faktore wat 'n invloed mag hê wanneer studente van die M.B.,Ch.B.- program die modules evalueer. Die volgende navorsingsvrae word aangespreek: • Hoe word die evaluering van modules geaffekteer deur die verandering in die studentesamestelling? • Is daar enige student-verwante faktore wat 'n invloed kan hê op die studente se evaluering van die MED 113-module se kwaliteit van onderrig? • Is daar enige spesifieke groepe studente in die voorgraadse opleiding wat spesiale aandag nodig het aangaande sekere fasette van onderrig? • Is daar enige aspekte in onderrig of sessies in die MED113-module wat drasties moet verander? Die doel van die studie was om 'n bydrae te lewer tot die kwaliteit van onderrig in die M.B.,Ch.B.-program van die Skool van Geneeskunde, Universiteit van die Vrystaat, en poog om 'n beter begrip van die resultate van die evaluasie deur die studente van die MED 113-module daar te stel, asook om sekere faktore wat moontlik geassosieerd mag wees met hulle evaluasies te identifiseer. Met behulp van die studente se evaluerings kan die sterk en swak punte van die MED 113- module geïdentifiseer en reggestel word, indien nodig. Die metode van ondersoek het die volgende behels: • 'n Literatuurstudie oor kwaliteitsversekering en die faktore wat moontlik 'n rol kan speel in die evaluering van onderrigkwaliteit deur studente is geloods. • Die ontwikkeling van 'n navorsingsinstrument (vraelys) om studente se persepsie van onderrigkwaliteit in die MED 113-module (Beginsels van Siekte en Gesondheid) te meet vir 2002, gebaseer op die inligting wat bekom is deur die literatuuroorsig. Hierdie instrumente is deur studente voltooi na elke sessie van die module. • Identifisering van faktore wat studente se evaluasie van onderrig beïnvloed, deur die inligting wat bekom is uit die vraelyste. • Die swak en sterk punte van die MED 113-module, volgens die studente se persepsie, is geïdentifiseer. • Aanbevelings is gemaak om die onderrig in die module te verbeter, gebaseer op die bevindings. Inligting wat deur hierdie studie versamel is, sal gebruik word in die beplanning van die MED 113-module vir 2004, asook vir toekomstige kwaliteitsversekeringstrategieë, met die oog op die verbetering van onderrig en opleiding in die Skool van Geneeskunde van die Universiteit van die Vrystaat.
Dissertation (M.HPE. (Health Professions Education))--University of the Free State, 2004
Keywords: Quality assurance; Under-graduate medical students; Assessments; Medical education; Factors influencing assessment; Internal self-evaluation; Medicine -- Study and teaching (Higher) -- South Africa -- Free State; Physicians -- Education; Medical education -- Evaluation